THE ROLE OF THE INTERNET AND MORAL PROPAGANDA IN THE INDOCTRINATION OF CHILDREN FOR NATIONAL FAMILY VALUES (American Journal of Research in Humanities and Social Sciences, 2023)
The article reveals the need to instill national family values in children in the modern conditions of globalization. In this regard, special attention is paid to the fact that the Internet and spiritual propaganda are the most effective means.